Relationship between Bone Morphogenetic Protein15 gene(BMP15) polymorphism and some productive and reproductive trait in Awassi sheep - AL-Saadi, B. Q; Al-Salihi, A. A.; AL-Anbari, N. N. (Journal of Kerbala for Agricultural Sciences, 2017)
In this study 50 ewes of native Awassi breed aging (2-5) years and their 62-offspring aging from birth to weaning was used and was carried in the department of animal production / Faculty of Agriculture / University of Baghdad , as well as laboratories of institute of genetic engineering and biotechnology for post graduate studies and over the period from 1/11/2015 to 1/6/2016. The aim of this study was to investigate the genotypes of Bone Morphogenetic Protein 15 (BMP 15) and their association with the production , growth and reproductive traits . PCR - RFLP analysis of (BMP 15) (153 bp) showed three various genotypes represented as AA , AC , and CC with frequencies 36.00, 40.00 and 24.00 respectively, the frequencies of the A and C alleles were 0.56 and 0.44, respectively, The results showed the effects of the genetic make-up of the BMP 15 gene has a high significant on fecundity ratio while no significant on fecundity rate , there was a variation of high significance of mortality rate in lambs up to weaning, with high significance in the rate of weight-gain variation in lambs from birth up to weaning and chest circumference and height were affected in relation to the variability of BMP 15 genotypes, The results of the current study showed that daily and total milk production of Awassi ewes was significantly increased in relation with variation of BMP 15 genotype in favor of ewes with genotype hybrid AC, moreover a significant variation in length of lactation periods, however, milk components were not significantly affected with variation of BMP 15 genotypes except the percentage of milk fat and in favor of ewes with genotype of AA. In conclusion through the study of gene expression of gene BMP15 could be open interesting prospects for future selection program and also improvement strategies to sheep to maximize the economic income of the election and breeding genotypes that have achieved the best fecundity and milk production.